Change of radioactive waste characteristics at their processing and storage at nuclear power plants - Rudychev, V.G.; Girka, I.O.; Rudychev, Y.V.; Kaplij, A.A.; Shchus, O.P.; Sokoltsova, T.O. (Вопросы атомной науки и техники, 2015)
This paper offers some methods developed for calculation of radiation from the casks for storage of radioactive wastes (RW) at the nuclear power plant (NPP) area. Monte Carlo method was used to calculate spectral-angular characteristics of the cask external radiation generated by separate nuclides. The obtained data allowed to provide simple methods for calculating changes in the radiation characteristics with the waste storage time and determining the radiation spatial distribution away from the casks. We propose a technique of reducing the radiation dose due to arranging properly loading the casks with barrels containing wastes of different activity. It is shown that at the RW storage its radiotoxicity decay is slower than the dose rate decay due to decrease of the activity of short-lived radionuclides.